The Influence of Human Resource Competencies, Utilization of Information Technology and Government Internal Control System on the Quality of SKPD Financial Reports in the Garut Regency Regional Government - Nugraha, Akhbar; Silviana, Silviana (Journal of Accounting and Finance Management, 2025)
This study aims to analyze the effect of human resource competence, utilization of information technology and government internal control system on the quality of SKPD financial statements in the Garut Regency Government. The population in this study were 75 Regional Work Units (SKPD) in the Garut Regency Government. The sample criteria are respondents who are representative financial staff from each SKPD.  The number of samples in the study were 75 respondents using the census technique. The type of data used is primary data. Hypothesis testing in this study includes validity test, reliability test, classical assumption test, multiple linear regression analysis test, t test and R2 test with the help of SPSS version 25. The results of the study can be concluded that human resource competence affects the quality of SKPD financial statements in the Garut Regency Government, utilization of information technology affects the quality of SKPD financial statements in the Garut Regency Government and the government internal control system affects the quality of SKPD financial statements in the Garut Regency Government.